2011
DOI: 10.1155/2011/698586
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Painful Crisis and Serum Zinc Level in Children with Sickle Cell Anaemia

Abstract: Sickle cell anaemia (SCA) is associated with zinc deficiency; zinc supplementation may ameliorate some of its clinical manifestations including the relief of painful crisis. Subjects and Methods. Serum zinc levels were determined in 71 children with SCA and painful crisis and in equal numbers in steady state. Seventy-one children with AA genotype acted as controls. Qualitative assessment of zinc content of 24-hour dietary recall and the last meal consumed before blood was drawn was taken. Serum zinc was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
4
20
2
Order By: Relevance
“…Our study found that zinc insufficiency/deficiency was significantly associated with increased pain crises at home and increased hospitalization due to VOC. Similarly, children with SCD‐related vaso‐occlusive bone crises have been found to have lower levels of zinc than those whom were not in pain crisis …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study found that zinc insufficiency/deficiency was significantly associated with increased pain crises at home and increased hospitalization due to VOC. Similarly, children with SCD‐related vaso‐occlusive bone crises have been found to have lower levels of zinc than those whom were not in pain crisis …”
Section: Discussionsupporting
confidence: 91%
“…More than half of our subjects were zinc insufficient/deficient, concordant with multiple studies indicating that patients with SCD have an increased risk of low zinc levels . There are numerous possible explanations as to why those with SCD have an increased risk of low zinc levels; it has been described that patients with SCD have an increased risk of hyperzincuria .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Instead, in Nepal, Zn deficiency was associated with both sex and age (25). The positive correlation between the Zn and Fe levels and HGB was also described in other studies (26,27). Iron deficiency is mainly reflected through low values of HGB, MCV, MCH, and MCHC, so the positive correlation is explainable (28).…”
Section: Discussionmentioning
confidence: 52%